Comparative Health Analysis Of Insurance Companies Owned By BUMN During The Covid-19 Pandemic In Indonesia - Shoviana, Evi; Rohmah, Farida (Business Management Analysis Journal (BMAJ), 2023)
This research aims to analyze and compare the financial health of government-managed Sharia insurance companies, both Sharia and non-sharia, which are included in BUMN during the COVID-19 pandemic. The data collection method in this research used a sample of ten insurance companies. The sampling technique in this research used purposive sampling. The data analysis method in the study uses paired difference test analysis (paired sample t-test). This research shows that ratios based on liquidity, ROA, ROE, RBC, Sharia, and non-Sharia insurance show healthy finances but not solvency ratios. Then, Sharia insurance companies and non-sharia state-owned companies have the same level of financial health. The limitations of this research are that several insurance companies need to have complete data used in research for two years because they look at financial health during the COVID-19 pandemic, the use of financial ratios in assessing the health of insurance companies still does not reflect the overall financial health condition, and the research sample is limited. It is hoped that future research can add operational and administrative aspects using quantitative and qualitative approaches, which have never been done so far, so the results will be better.